Popular religion and ascetic practices: new studies on Mahimā Dharma - Beltz, Johannes (Manohar Publishers & Distributors, 2008)
Contributed research papers presented at an international seminar organized by Dept. of Anthropology, Utkal University, Bhubaneswar on 23 Feb, 2002, on Mahima Dharma of Orissa and on the work and philosophy of Bhima Bhoi